2013
DOI: 10.3727/096368912x659899
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell-Based Therapy for Pulmonary Arterial Hypertension

Abstract: A growing body of evidence in animal models and clinical studies supports the concept that endothelial progenitor cell (EPC)-mediated therapy ameliorates pulmonary arterial hypertension (PAH) and thus may represent a novel approach to treat it. Conversely, several experimental findings suggest that EPCs may be involved in PAH pathogenesis and disease progression. These discrepant results confuse the application of EPC transplantation as an effective treatment strategy for PAH. To improve the study of EPC trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…Meanwhile, the elevated level of TNF-α may represent a hostile microenvironment which may induce EPCs differentiation into abberant cells [33]. So drug regimen before or in combination with cell transplantation may be a promising strategy for the future EPC therapy for cardiovascular diseases [33]. The purpose of this study was to examine the effect of Tan IIA on expression of adhesion molecules in TNF-α-induced EPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the elevated level of TNF-α may represent a hostile microenvironment which may induce EPCs differentiation into abberant cells [33]. So drug regimen before or in combination with cell transplantation may be a promising strategy for the future EPC therapy for cardiovascular diseases [33]. The purpose of this study was to examine the effect of Tan IIA on expression of adhesion molecules in TNF-α-induced EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α was found to reduce proliferation, adhesion, migration and tube formation ability of EPCs [32]. Meanwhile, the elevated level of TNF-α may represent a hostile microenvironment which may induce EPCs differentiation into abberant cells [33]. So drug regimen before or in combination with cell transplantation may be a promising strategy for the future EPC therapy for cardiovascular diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the recently concluded pulmonary hypertension and angiogenic cell therapy (PHACeT) trial, endothelial nitric oxide synthase (eNOS)‐transfected eEPCs were systemically administered to patients with pulmonary arterial hypertension (PAH) [54]. EPC injections have previously been shown to stimulate endothelial repair and ameliorate PAH conditions [55], and in the PHACeT trial, the use of eNOS‐augmented eEPCs was expected to have increased vasodilatory and vasoregenerative effects. Modest improvements in quality of life measures were observed in patients following treatment, although these could not be sustained, and the group was unable to ascertain the safety or efficacy of this approach.…”
Section: Clinical Application Of Epcs In Regenerative Medicinementioning
confidence: 99%
“…These cells do not express markers which are characteristic of mature endothelial cells and are not involved in lumen formation ( 7 , 8 ). Increasing evidence has suggested that EPCs have a role in the endothelial repair process through differentiation into mature ECs and the release of protective paracrine factors, including vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF) ( 9 ). Therefore, improving EPC number and function through pharmacological modulation may be a novel strategy for atherosclerosis prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%